PERSEPSI MAHASISWA ILMU KOMUNIKASI FIS UIN SU STAMBUK 2017-2021 MENGENAI KONTEN VIDEO LGBT DAN NIKAH BEDA AGAMA DALAM AKUN YOUTUBE DEDDY COURBUZIER (Study Deskriptif Kualitatif “LGBT dan Nikah Beda Agama!!Double Kill!-Somasi-Adriano Qalbi – Deddy Corbuzier Podcast”) - Anisa Dinda Adityana; Muhammad Husni Ritonga, Muhammad Alfikri (Jurnal Komunikasi, 2024)
This research is entitled " Analisis Framing Tentang Poligami dalam Video “Persepsi Mahasiswa Ilmu Komunikasi FIS UIN SU Stambuk 2017-202 Mengenai Konten Video LGBT Dan Nikah Beda Agama Dalam Akun YouTube Deddy Courbuzier ". The purpose of this research is to find out the influence, perceptions and effects felt by Communication Science Students on the Somasi video content on Deddy Corbuzier's YouTube Channel. The theories used are Perception Theory and Mass Communication Effects Theory. The research object is the video "LGBT and Interfaith Marriage!! Double Kill!-Somasi-Adriano Qalbi - Deddy Corbuzier Podcast". The method used in this research is a qualitative method using specific procedures and methodology. The analysis technique used is in the form of sentences or words from interviews or observations. The research results show that students can receive information in the content and students can actively participate in validating the truth of the data conveyed in the video